2001
DOI: 10.1074/jbc.m104597200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine-specific Phospholipase A1Stimulates Histamine Release from Rat Peritoneal Mast Cells through Production of 2-Acyl-1-lysophosphatidylserine

Abstract: Lysophosphatidylserine (1-acyl-2-lyso-PS) has been shown to stimulate histamine release from rat peritoneal mast cells (RPMC) triggered by Fc⑀RI (high affinity receptor for IgE) cross-linking, although the precise mechanism of lyso-PS production has been obscure. In the present study we show that phosphatidylserine-specific phospholipase A 1 , PS-PLA 1 , stimulates histamine release from RPMC through production of 2-acyl-1-lyso-PS in the presence of Fc⑀RI cross-linker. The potency of 2-acyl-1-lyso-PS was almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 32 publications
0
55
1
3
Order By: Relevance
“…Lyso-PS Are Abundant Modified PS Species Generated in Neutrophils Stimulated to Activate the NADPH Oxidase-The signaling potential of lyso-PS was first recognized in its description as a potent mast cell secretagogue, and it has subsequently been given signaling roles in other settings (20,21,39,55,56). Here, we have shown that lyso-PS species were generated in vitro and in vivo as major modified PS species in neutrophils stimulated to activate the NADPH oxidase.…”
Section: Discussionmentioning
confidence: 82%
“…Lyso-PS Are Abundant Modified PS Species Generated in Neutrophils Stimulated to Activate the NADPH Oxidase-The signaling potential of lyso-PS was first recognized in its description as a potent mast cell secretagogue, and it has subsequently been given signaling roles in other settings (20,21,39,55,56). Here, we have shown that lyso-PS species were generated in vitro and in vivo as major modified PS species in neutrophils stimulated to activate the NADPH oxidase.…”
Section: Discussionmentioning
confidence: 82%
“…We chose PS-PLA 1 as an enzyme to produce 2-acyl-1-LysoPS on the cell surface. PS-PLA 1 specifi cally cleaves PS and is capable of cleaving PS on the outer surface of plasma membrane without any effect on cell viability ( 15 ). When HEK293 cells were treated with recombinant PS-PLA 1 , a signifi cant amount of 2-oleoyl-1-LysoPS and a lesser amount of 2-DHA-1-LysoPS were detected in the cells but not in the cell supernatant.…”
Section: Albumin Accelerates Acyl Migrationmentioning
confidence: 99%
“…This is even more true of another member of the lipase gene family, phosphatidylserine phospholipase A1, which has an absolute preference for phosphatidylserine and lysophosphatidylserine (10). The function of these two lipases is uncertain at this time, though endothelial lipase is believed to have a role in HDL metabolism (7)(8)(9), while phosphatidylserine phospholipase A1, produced by platelets, may act in response to apoptotic conditions by stimulating mast cell histamine release, thereby contributing to inflammation (25,26).…”
Section: Functionsmentioning
confidence: 99%